Pengembangan Media Animation Series Terintegrasi Education for Sustainable Development Untuk Memfasilitasi Visualization Learning Pada Materi Energi Terbarukan - Agni Yusifa; Asep Saefullah; Rahmat Firman Septiyanto (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
This research was conducted against the backdrop of the emergence of problems in the use of fossil energy which caused Indonesia to have an energy crisis. Education is one of the efforts to prevent the energy crisis. Therefore, research on the development of teaching media integrated with Education for Sustainable Development (ESD) was conducted. The purpose of this study was to determine the results of material and media validation and students' responses to the acceptance of teaching media. This research has developed ESD integrated animated video teaching media to facilitate visualisation learning on renewable energy material. This research method uses R&D with Thiagarajan's modified 4-D research model with stages namely define, design and development. This research. The results of material expert validation obtained a percentage of 83.7% which was categorised as very feasible and media validation obtained a percentage of 85.4%. Student response to teaching media obtained a percentage of 87.7% which is categorised as very good.